Do Australian drivers give female cyclists more room when passing?. (June 2018) - Haworth, Narelle; Heesch, Kristiann C.; Schramm, Amy; Debnath, Ashim Kumar
Abstract: Cycling has demonstrated health benefits, but the fear of collisions with motor vehicles discourages many people from riding on the road, particularly women. Previous studies have reported mixed results about the factors influencing the distances left by drivers when passing cyclists. The present research aimed to control for other rider, roadway and traffic factors to understand whether cyclist gender influences passing distances. Video recordings of 1113 passing events (865 males, 248 females) occurring in Southeast Queensland, Australia after the introduction of a minimum passing distance road rule were analysed. Events were at sites with narrow or wide lanes and 40 or 60 km/h speed zones. Linear mixed modelling was used to examine the association between gender of the cyclist and the passing distance, after adjusting for rider characteristics (clothing type, riding single file or two or more abreast), the type of overtaking vehicle, the time of the observation (time of day, weekday or weekend), and the site characteristics (speed zone and lane width). In the modelling, observations were nested within the date of observation. No significant relationships between gender and passing distance or interactions between gender and the other factors were found. Passing distance appears to be influenced by cyclists' clothing, vehicle type, traffic volumes, and speed limits. Greater passing distance was given to cyclists who wore street clothes (versus lycra). Motorcycle or scooter riders gave more passing distance than did drivers of small passenger vehicles. Passing distance was also greater when overtaking occurred during morning peak (versus evening peak), and in 60 km/h speed zones (versus 40 km/h speed zones). The results do not support the findings of previous studies that drivers give more space when overtaking female cyclists. Highlights: Fear of motor vehicle collisions discourages cycling, particularly for women. Previous passing distance studies show mixed results regarding influencing factors. Gender did not influence observed passing distance in this study. Greater passing distance when wearing street clothes. Greater distance for motorcycles, morning peak, higher speed zone.